Investigation of the reasons for the employee turnover of parkinson's patients - OĞUZ, SEMRA; POLAT, MİNE GÜLDEN (My University, 2022)
Purpose: It is known that early retirement has been increasing for patients with Parkinson\"s disease. The data on the factors that cause early retirement in this patient population is limited. The objective of this study is to analyze the effects of Parkinson\"s disease that cause early retirement.
Keywords: REHABİLİTASYON; Klinik Tıp; Klinik Tıp (MED); REHABILITATION; CLINICAL MEDICINE; Clinical Medicine (MED); Early-Retirement; Employee Turnover; Motor Symptoms; Non-Motor Symptoms; Parkinson's Disease; DISEASE; ONSET